2011
DOI: 10.4315/0362-028x.jfp-10-484
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Colonized Beef Cattle Populations Fed Combinations of Yeast Culture and an Ionophore in Finishing Diets Containing Dried Distiller’s Grains with Solubles Had Similar Fecal Shedding of Escherichia coli O157:H7

Abstract: Beef steers (n = 252) were used to evaluate the effects of dietary supplement on fecal shedding of Escherichia coli O157:H7. Seven pens of 9 steers (63 steers per treatment) were fed diets supplemented with or without yeast culture (YC) or monensin (MON) and their combination (YC × MON). YC and MON were offered at 2.8 g/kg and 33 mg/kg of dry matter intake, respectively. Environmental sponge samples (from each pen floor, feed bunk, and water trough) were collected on day 0. Rectal fecal grab samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This agrees with previous studies of naturally colonized cattle, which showed that feeding cattle 22.5% CDDGS or WDDGS had no effect on prevalence or concentration of E. coli 0157:H7 in feces (8,12,27). Si milarly, Jacob et al (17) determined that there was no difference among cattle fed 20% wet or dry com distillers' grains and control but that cattle fed 40% DDGS had a higher prevalence and more high-shedders at certain stages of feeding.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This agrees with previous studies of naturally colonized cattle, which showed that feeding cattle 22.5% CDDGS or WDDGS had no effect on prevalence or concentration of E. coli 0157:H7 in feces (8,12,27). Si milarly, Jacob et al (17) determined that there was no difference among cattle fed 20% wet or dry com distillers' grains and control but that cattle fed 40% DDGS had a higher prevalence and more high-shedders at certain stages of feeding.…”
Section: Discussionsupporting
confidence: 89%
“…An increase in protein digestion can also lead to elevated ammonia concentrations in the hindgut, providing a more hospitable environment for some E. coli 0157:H7 strains (14). The nutrient composition of DDGS varies with DDGS type and bioethanol plant origin (27), which may increase variability of shedding of the organism, leading to contradictory results among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Following abstract screening, there were 28 publications eligible for full‐text screening. Subsequent exclusions included: one full‐text citation and a thesis that could not be obtained; one full text publication was not amenable to data extraction (Swyers et al., ); eight publications were conducted as challenge trials; and two publications were reports of studies published elsewhere, thus duplicates. The final number of publications for the systematic review and meta‐analysis that met the inclusion and exclusion criteria was 16 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The early emphasis of preharvest food safety research was based on the hypothesis that the emergence of E. coli O157 disease in humans resulted from relatively recent changes in cattle management practices that favored this pathogen. Examples of such management practices included increased grain components in cattle feeds (4,5), the use of antimicrobial drugs and other growth-promoting feed additives (6)(7)(8)(9)(10)(11), increased intensity of cattle production, rearing larger herds and increased confinement (12)(13)(14)(15)(16), and (17)(18)(19). Unfortunately, however, each of these attractive hypotheses has since either been refuted or shown to have only minor influence on cattle infection with E. coli O157, as described in several comprehensive recent reviews (20)(21)(22)(23).…”
Section: Can Live Cattle Be Managed To Reduce or Prevent E Coli O157mentioning
confidence: 99%